SUPERIOR ANTIBACTERIAL PROPERTIES OF COPPER-BEARING HIGH ENTROPY ALLOY COATED STAINLESS STEEL SURFACE FABRICATED USING LASER CLADDING (Jurnal Teknologi (Sciences & Engineering), 2024)
A high-entropy alloy (HEA) coating is applied to a stainless-steel surface using the laser cladding (LC) process. This coating offers a broad-spectrum antibacterial ability and favorable mechanical properties. The release of copper ions from the HEA effectively inhibits the growth of Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus), enhancing the alloy’s suitability for various applications requiring antibacterial properties. The elemental compositions, sizes, and morphologies of the constructed HEAs are revealed through X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray analysis (EDX). This study validates the feasibility of applying the antibacterial CoCrFeCuNi HEA alloy coating to stainless steel via LC. The antibacterial evaluation showcases the enhanced efficacy of the CoCrCuFeNi HEA coating, demonstrating an antibacterial effectiveness of approximately 89% against E. coli and 98% against S. aureus. In contrast, the CoCrFeNi HEA coating exhibits an antibacterial effectiveness of about 40% against E. coli and 93% against S. aureus. The Vickers hardness of the stainless steel coated with CoCrCuFeNi HEA has significantly increased to 352 HV, compared to the CoCrFeNi coating with a hardness of 300.6 HV and the uncoated stainless steel with a hardness of 256.6 HV. This HEA alloy demonstrates considerable potential for use in medical applications or other settings that require antibacterial features.